Impact of Heterotopic Ossification on Functional Recovery in Acute Spinal Cord Injury - Franz, Steffen; Rust, Lukas; Heutehaus, Laura; Rupp, Rüdiger; Schuld, Christian; Weidner, Norbert (Frontiers in Cellular Neuroscience, 2022)
Objective: In spinal cord injury (SCI), heterotopic ossification is a frequent secondary complication, commonly associated with limited range of motion of affected joints, which could lead to secondary disability in activities of daily living. Additionally, heterotopic ossifications might challenge the effect of regeneration-promoting therapies on neurological and functional recovery. This study evaluated the impact of heterotopic ossification on clinical recovery within the first year after SCI. Methods: The study was conducted as a monocentric longitudinal paired cohort study. Recruitment was based on consecutive sampling in the framework of the European Multicenter about Spinal Cord Injury (EMSCI). Recovery profiles were determined using standardized neurological and functional clinical assessments within the first year following SCI. All study participants underwent at least two comprehensive standardized neurological and functional clinical examinations according to the International Standards for Neurological Classification of SCI and the Spinal Cord Independence Measure, respectively. Data regarding the diagnosis and treatment of heterotopic ossification were obtained by reviewing the patient medical records. The most similar "digital twin" from the entire EMSCI database was matched in terms of age, acute neurological and functional status to each individual with SCI and heterotopic ossification. Results: Out of 25 participants diagnosed with heterotopic ossification, thirteen individuals were enrolled and matched to control individuals. Most individuals presented with motor complete injury (75%). Ossifications were most frequently located at the hip joints (92%) and mainly occurred within the first three months after SCI. Individuals with heterotopic ossification achieved around 40% less functional improvement over time compared to their matched counterparts, whereas neurological recovery was not altered in individuals with SCI and heterotopic ossification. Conclusion: Heterotopic ossification – a common complication of SCI – unfavorably affects functional recovery, which in the end is most relevant for the best possible degree of independence in activities of daily living. Upon presentation with heterotopic ossification, neurological improvement achieved through potential restorative therapies might not translate into clinically meaningful functional improvement. Diagnostic algorithms and effective early prevention/treatment options for heterotopic ossification need to be established to ensure best possible functional outcome. Clinical trial registration number: NCT01571531 (https://clinicaltrials.gov)